Moh's example of algebroid space curves. (May 2021) - Mehta, Ranjana; Saha, Joydip; Sengupta, Indranath
Abstract: In this paper we revisit the family of algebroid space curves defined by Moh and find an explicit minimal generating set for the defining ideal.